(untitled) (Hoboken, N.J., 2007)
This comprehensive resource covers the fundamentals, formulation, and biopharmaceutical issues of lipid-based drug delivery. It presents the principles of lipid absorption and covers formulation issues, such as dissolution testing and stability testing, and physiological and biopharmaceutical issues, including the role of specific enzymes, the evaluation of transport systems in the body, and the mechanisms governing the transport of water-insoluble drugs.
Keywords: Lipids,Excipients,Drugs,Pharmaceutical solutions; Therapeutic use,Dosage forms